Evaluation of lifestyle and quality of life in the elderly: a literature review - Luana Karoline Ferreira; Juliana Fernandes Filgueiras Meireles; Maria Elisa Caputo Ferreira (Revista Brasileira de Geriatria e Gerontologia, 2018)
Abstract Objective: to analyze Brazilian and non-Brazilian scientific production that considers the relationship between the lifestyle and quality of life of the elderly. Method: an integrative review of literature was performed in the Scopus, PubMed, Virtual Health Library and PsycINFO databases. Four cross-searches were adopted: the English synonyms of the word "elderly" ("Aged", "Aging", "Old age" and "Elderly") with the terms "Quality of life" and "Lifestyle". Results: after the adoption of the inclusion and exclusion criteria, 21 articles were analyzed. Physical activity, diet, body composition, alcohol intake, smoking and social relations were the main components of lifestyle investigated. The studies show that these factors influence the perception of the quality of life of the elderly. In addition to these factors, sociodemographic characteristics, functional capacity, sleep quality and comorbidities are also factors that influence the quality of life of the elderly. Conclusion: interest in the relationship between the lifestyle and quality of life of the elderly has increased in recent years. It was observed that the lifestyle of the elderly has been investigated in several ways, however no qualitative studies were found using the search criteria adopted in this review. As future perspectives, it is hoped that tools for evaluating the lifestyle of the elderly will be developed and qualitative investigations will be carried out in order to obtain a deeper understanding of the specificities that exist in the relationship between the lifestyle and levels of quality of life in old age.